Involving Students’ Opinion in Actual and Preferred Teacher Interpersonal Behavior and Their Attitude Towards Science Subject - Mustafa Kamal Nasution (Institut Agama Islam Negeri Imam Bonjol Padang, 2016)
This study aims to investigate the student perception on teacher interpersonal behavior and their attitude toward science subject. 207 respondents were involved, consisted of 200 students in 10-12 grade and 7 science teachers of public high school in Aceh. Two types of questionnaires were used namely the Indonesian version of the questionnaire of teacher interaction (QTI) and test of science related attitude (TOSRA). SPSS program were applied to process the data statistically. First, the reliability of questionnaires is measured using descriptive statistics of all and each scale of QTI. Second, the difference between students’ perceptions on the actual and ideal teacher interpersonal behavior was computed by Paired Sample t-tests. Third, the relationship between students' perception on teachers’ interpersonal behavior and students' attitudes towards science subjects was compared using multiple regression analysis-standardized regression coefficient β. The finding showed that the Indonesian version of questionnaire of teacher interaction (QTI) is reliable (αC = 0.86), to be applied to the high school students in the regency. It is generally seen that the students consider their teachers demonstrate more positive interpersonal behavior than the negative. However, it is clearly seen that between actual and ideal perceptions on the whole scale of QTI is significantly different. Last, from the three scales of teacher interpersonal behavior, helping/friendly, dissatisfaction, and admonishing appeared influential, only the helping/friendly scale significantly correlate (at the .05 level) with student attitudes toward science subject.